1997
DOI: 10.1016/s0092-8674(00)81848-6
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin: An Endogenous Inhibitor of Angiogenesis and Tumor Growth

Abstract: We previously identified the angiogenesis inhibitor angiostatin. Using a similar strategy, we have identified endostatin, an angiogenesis inhibitor produced by hemangioendothelioma. Endostatin is a 20 kDa C-terminal fragment of collagen XVIII. Endostatin specifically inhibits endothelial proliferation and potently inhibits angiogenesis and tumor growth. By a novel method of sustained release, E. coli-derived endostatin was administered as a nonrefolded suspension. Primary tumors were regressed to dormant micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

56
2,796
4
62

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,075 publications
(2,918 citation statements)
references
References 33 publications
56
2,796
4
62
Order By: Relevance
“…54,55 All current treatments (surgical, laser and photodynamic therapy) merely delay severe vision loss, because they are directed at destroying new vessels but do not address the underlying angiogenic stimuli that frequently cause recurrences. 56 Currently, there are no antiangiogenic treatments available for patients with ocular neovascularization, but several new approaches such as intraocular injections of an aptamer that binds VEGF or an anti-VEGF antibody 57 or proteins with antiangiogenic activity [58][59][60] are being considered. Recombinant AAVmediated gene transfer offers an alternative for local sustained delivery of antiangiogenic proteins to intraocular tissues.…”
Section: Gene Transfer In Animal Models Of Retinal Degenerationmentioning
confidence: 99%
“…54,55 All current treatments (surgical, laser and photodynamic therapy) merely delay severe vision loss, because they are directed at destroying new vessels but do not address the underlying angiogenic stimuli that frequently cause recurrences. 56 Currently, there are no antiangiogenic treatments available for patients with ocular neovascularization, but several new approaches such as intraocular injections of an aptamer that binds VEGF or an anti-VEGF antibody 57 or proteins with antiangiogenic activity [58][59][60] are being considered. Recombinant AAVmediated gene transfer offers an alternative for local sustained delivery of antiangiogenic proteins to intraocular tissues.…”
Section: Gene Transfer In Animal Models Of Retinal Degenerationmentioning
confidence: 99%
“…9,14 Endostatin inhibits tumor angiogenesis by interfering at multiple levels of the growth factor signaling for endothelial cell proliferation, migration, and vessel formation. 10,15,16 Previously, we have shown a significant treatment effect in orthotopic human RCC (Caki-2 ) xenografts in a nude mouse model 17 using intratumoral HSV-tk gene therapy. Neither HSV-tk adenovirus in the absence of GCV, nor GCV coupled with an adenovirus containing a LacZ marker gene had any antitumor effect.…”
mentioning
confidence: 99%
“…Endostatin is a dose-dependent, specific inhibitor of endothelial cell growth (O'Reilly et al, 1997). Recent in vitro studies using DNA and antibody array have identified its antiangiogenic effects on microvascular endothelial cells (Abdollahi et al, 2004).…”
mentioning
confidence: 99%